Underwater manipulators: A review. (1st September 2018) - Sivčev, Satja; Coleman, Joseph; Omerdić, Edin; Dooly, Gerard; Toal, Daniel
Abstract: This paper describes the state-of-the art in the area of underwater robot manipulator systems. A brief introduction is given on the use of manipulators in various offshore industries for different subsea intervention applications. It provides a comprehensive summary of existing commercial and prototype underwater manipulators, covering relevant aspects such as design features, their capabilities and merits, and provides a detailed comparison. This is followed by a thorough analysis of advantages and disadvantages of both electrically and hydraulically actuated manipulators. Furthermore, a detailed description of commercially available underwater manipulator control systems is presented in order to provide a realistic picture of the existing technology and its limitation. In addition, an extensive bibliography covering research results in the field of control algorithms is presented, including low level motion control, high level kinematic control and motion planning schemes along with the implementation issues. Highlights: State-of-the-art in the area of underwater manipulator systems is presented with a comprehensive literature review. An extensive summary of existing systems is provided, followed by a thorough analysis. A realistic picture of the existing technology and its limitations are presented. Critical performance-limiting factors to be considered during the design of future systems are identified.